2019
DOI: 10.1158/1078-0432.ccr-19-0832
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bcl-2 Synergistically Enhances the Antileukemic Activity of Midostaurin and Gilteritinib in Preclinical Models of FLT3-Mutated Acute Myeloid Leukemia

Abstract: Purpose: To investigate the efficacy of the combination of the FLT3 inhibitors midostaurin or gilteritinib with the Bcl-2 inhibitor venetoclax in FLT3-ITD acute myeloid leukemia (AML) and the underlying molecular mechanism. Experimental Design: Using both FLT3-ITD cell lines and primary patient samples, annexin V-FITC/propidium iodide staining and flow cytometry analysis were used to quantify cell death induced by midostaurin or gilteritinib, alone or in combination with venetoclax. Western blot analysis was p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 37 publications
5
111
0
Order By: Relevance
“…Using multiple, orthogonal approaches, we validated the synergistic relationship between the effects of BCL2 and FLT3 inhibition that was predicted by our previous work [11] and expanded preclinical work by Ma et al [12] using genetic validation and clinical-grade inhibitors that could be more readily translated to the clinic as combination strategies. We showed that depletion of BCL2 via both gene silencing and chemical inhibition in addition to FLT3 inhibition increased cell death in FLT3-ITD cell lines and primary AML patient samples beyond that of each perturbation alone, an effect which was not observed to the same extent in the case of FLT3-WT.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Using multiple, orthogonal approaches, we validated the synergistic relationship between the effects of BCL2 and FLT3 inhibition that was predicted by our previous work [11] and expanded preclinical work by Ma et al [12] using genetic validation and clinical-grade inhibitors that could be more readily translated to the clinic as combination strategies. We showed that depletion of BCL2 via both gene silencing and chemical inhibition in addition to FLT3 inhibition increased cell death in FLT3-ITD cell lines and primary AML patient samples beyond that of each perturbation alone, an effect which was not observed to the same extent in the case of FLT3-WT.…”
mentioning
confidence: 72%
“…1 a), prompting further validation study of the combination of FLT3 and BCL2 inhibitors. Previous work by Ma et al [ 12 ] also showed the in vitro effects of combining FLT3 and BCL2 inhibitors. This work stemmed from the observation that FLT3 inhibitors result in downmodulation of the expression of myeloid cell leukemia 1 (MCL1), a known mechanism of resistance to BCL2 inhibitors, and could improve activity of BCL2 inhibitors.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Here, we introduce several combinations that can reduce the MCL-1 level indirectly to circumvent the resistance. Indirect MCL-1 inhibitors include the following compounds: bromodomain extra-terminal protein inhibitors (BETis), which reduce MCL-1 and BCL-XL levels while increasing BIM levels and enhance the lethal effects of venetoclax on AML ( 97 ); cyclin-dependent kinase 9 (CDK9) inhibitors, which inhibit the transcription of MCL-1 ( 98 ); midostaurin or gilteritinib, FLT3 inhibitors that induce downregulation of MCL-1 to increase venetoclax activity ( 99 ); CUDC-907, a dual PI3K and histone deacetylase inhibitor that downregulates MCL-1, upregulates BIM, and induces DNA damage ( 100 ); MEK inhibitors ( 101 ); MDM2 inhibitors ( 102 ); PI3K inhibitors ( 103 ); and selinexor, an XPO1-selective inhibitor ( 104 ). In addition, an inhibitor of the Nedd8-activating enzyme (MLN4924) can upregulate Noxa, and 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCR) inhibitors (statins) can upregulate PUMA.…”
Section: Venetoclax Resistance and Combination Strategies To Overcomementioning
confidence: 99%
“…Furthermore, we examined genes coding for known interacting partners of XPO1 from literature [ 15 , 16 , 17 , 18 ] and the comprehensive database NESdb [ 19 ] and found that the effect of the knockout of many of these genes was also predicted to be synergistic with midostaurin ( Figure 1 e; Table 1 ); the depletion was especially strong for Karyopherin-β1 (KPNB1) and Baculoviral IAP Repeat Containing 5 (BIRC5). BCL2 inhibition with venetoclax has been already shown to sensitize FLT3 -mutated AML cell lines to gilteritinib [ 20 ]. A Phase 1b study of venetoclax and gilteritinib in patients with Relapsed/Refractory AML also demonstrated efficacy, with 50% of FLT3-mutant patients achieving composite complete remission and an additional 40% reaching a morphologic leukemia-free state [ 21 ].…”
Section: Resultsmentioning
confidence: 99%